THE IMPLEMENTATION IMPLEMENTASI SUPERVISI AKADEMIK DALAM MENDORONG OPTIMALISASI PLATFORM PEMBELAJARAN BERBASIS DIGITAL DI SEKOLAH DASAR - Hardian Saputra, Hardian Saputra; Ahmad Hariandi, Ahmad Hariandi; Muhammad Sholeh, Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of academic supervision in encouraging the optimization of digital learning platforms in elementary schools. The research was conducted at SDN 001/V Kuala Tungkal using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that well-planned, collaborative, and continuous academic supervision plays a significant role in improving teachers’ competence in utilizing digital learning platforms. Through academic supervision, teachers receive guidance in planning, implementing, and evaluating digital-based learning, so that the use of digital learning platforms is not merely technical but also pedagogical. Academic supervision also encourages teachers to become more reflective and innovative in developing interactive learning activities that are appropriate to the characteristics of elementary school students